Analisis Beban Kerja Fisiologis dan Mental Mahasiswa pada Simulasi Lingkungan Kerja di Laboratorium Ergonomi Menggunakan Pendekatan Macroergonomics Analysis of Structure - Firdaus, Aqfi Nur; Yasin, Nurnianingsih A; Daud, Parlan S; Mohamad, Silvana; Bukamo, Richard Renaldy (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study analyzes the physiological and mental workload of students in a simulated work environment at the Ergonomics Laboratory using the Macroergonomics Analysis of Structure (MAS) approach. The simulation exposed 21 participants to a combination of grinding machine noise (90 dB) and low lighting (10 Lux) for 40 minutes. The results indicate that the simulated work environment significantly increased physiological workload, evidenced by an increase in pulse rate where 38% of participants exhibited a %CVL above 15% (category "Improvement Required") and two participants even reached the "Heavy" category (>30%). Mentally, 85.7% of participants reported a high to very high workload based on NASA-TLX measurements. MAS analysis identified systemic s between the technological, physical environment, and personnel subsystems as the root cause of the problem. This study recommends improvements, including environmental modifications, task design adjustments, and the implementation of integrated OSH policies to create an ergonomic, healthy, and sustainable work system.